2020
DOI: 10.1039/d0ra07162e
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of copper nanoparticles encapsulated by nitrogen-doped graphene at room temperature via solution plasma

Abstract: An excellent corrosion protection for copper nanoparticles by nitrogen-doped few-layer graphene via solution plasma process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Many researchers have studied carbon synthesis and deposition on materials using plasma processes, including nanographene synthesis using alcohol in-liquid plasma. Nitrogen-doped carbon has also been synthesized on metal nanoparticles using plasma in solutions containing organic compounds such as N,N -dimethylformamide. , Furthermore, as low-pressure plasma processes, various diamond-like carbons have been synthesized by plasma-enhanced chemical vapor deposition, and the direct growth of graphene on hBN by plasma-assisted molecular beam epitaxy has been reported. , In our previous studies, the modification of hBN particles by plasma in hydroquinone aqueous solution was found to improve their dispersibility in water and a polymer matrix with maintaining the thermal conductive and electrical insulating properties as fillers, , but the surface state was not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied carbon synthesis and deposition on materials using plasma processes, including nanographene synthesis using alcohol in-liquid plasma. Nitrogen-doped carbon has also been synthesized on metal nanoparticles using plasma in solutions containing organic compounds such as N,N -dimethylformamide. , Furthermore, as low-pressure plasma processes, various diamond-like carbons have been synthesized by plasma-enhanced chemical vapor deposition, and the direct growth of graphene on hBN by plasma-assisted molecular beam epitaxy has been reported. , In our previous studies, the modification of hBN particles by plasma in hydroquinone aqueous solution was found to improve their dispersibility in water and a polymer matrix with maintaining the thermal conductive and electrical insulating properties as fillers, , but the surface state was not clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Since the synthesis methods of Cu@G NPs reported in the literature have produced multi-layer graphene shells for Cu NPs, 41,[46][47][48]53 the variation in the k concerning the number of layers per flake was studied and reported in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, the reported protocols consist of depositing C atoms on Cu NPs, eventually forming a graphene cover. 40,41,[46][47][48][49][50][51][52][53] However, to our knowledge, no techniques have been proposed to produce Cu@G NPs in steps, i.e., generating the Cu NPs and graphene flakes separately and then putting them together in a single medium. Our results suggest that, in these cases, it would not matter if the adsorption of the flakes on the NPs occurs planar one by one or if they first form a stack and then adsorb perpendicularly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the tips of electrodes in the HCl solution increased from 0.1 mm to 0.17 mm, while 0.12 mm and 0.15 mm were observed in the KCl and KOH solution, respectively. Accordingly, it suggested that acidity has a significant influence on the sputtering of metal electrodes in the SPP, which is considered as an advantage for the synthesis of metal-based nanoparticles without using precursors and reducing agents [ 32 , 38 , 57 ]. Furthermore, the investigation on the formation of • OH was also conducted via the time-resolved optical emission measurement at various time delays to the positive voltage pulse in the range of 0–38 μs.…”
Section: Solution Plasma Process (Spp): Chemistry and Influencing Parametersmentioning
confidence: 99%